Discourses of Volunteer Farm Tourism in Nepal: A Methodological Approach to World Wide Opportunities on Organic Farms - Wengel, Yana (Journal of Tourism & Adventure, 2018)
In this research note, I propose an appropriate methodology to study discourses around the volunteer farm exchange programme World Wide Opportunities on Organic Farms (WWOOF) in Nepal. WWOOF is an international movement that connects organic farmers and international travellers who wish to exchange their labour for food and accommodation. Previously WWOOF was described as volunteer tourism, alternative tourism or as an alternative to tourism. As a non-profi t exchange programme WWOOF abodes the commercialisation of tourism and attracts long-term international travellers who do not describe themselves as tourists and see WWOOF as a way to explore the destinations off the beaten track. As such, WWOOF members share different philosophy or discourse of travel from commercial farm tourism. Thus, it is essential to understand what drives farm hosts and volunteers to participate in this unique exchange programme in Nepal.